Adalimumab induced psoriasis during the treatment of inflammatory bowel disease – case report - Lelonek, Edyta; Dębicka, Magdalena; Maj, Joanna; Hryncewicz-Gwóźdź, Anita; Matusiak, Łukasz (Dermatology Review/Przegląd Dermatologiczny, 2015)
Introduction. Anti-tumor necrosis factor α (anti-TNF-α) antibodies are used to treat immune-mediated inflammatory diseases (IMID), which include inflammatory bowel diseases or psoriasis. In the group of adverse events induced by anti-TNF agents we can observe psoriatic lesions. Case report . We present two women who in the course of therapy of Crohn's disease with adalimumab (ADA) developed psoriasis. Diagnosis was based on the clinical picture and confirmed by histopathological examination. In the first case, treatment with ADA was continued and topical therapy was started, with a good effect. The second patient abandoned ADA therapy and the skin lesions resolved due to the external treatment, too. Conclusions . The comorbidity of IMID creates therapeutic difficulties and requires further study to elucidate pathophysiology of these diseases, as well as to clarify the mechanism of action of anti-TNF agents.